SEJARAH DAN DINAMIKA KONFLIK ANTARA PERGURUAN PENCAK SILAT SETIA HATI TERATE DAN SETIA HATI WINONGO DI KABUPATEN MADIUN - , Dany Rosanty; , Dr. Nanang Pamuji Mugasejati ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims to look at the history and conflicts dynamics between two traditional martial groups, Setia Hati (SH) Terate and Setia Hati (SH) Winongo. The research focused on the conflict in 2007 in Madiun, East Java. Elders from traditional martial groups, security forces, military and police, local government officials, community leaders, and members of IPSI (Ikatan Pencak Silat Indonesia) had been interviewed for their perception in this matter. The research shows that the conflict occurs in regular basis every year. It happens at the time were annual community ritual takes places, namely: Keceran or Sah-sahan, Hala bi halal, and Syuro. This research founds there are history and economic, social, political aspects as structural factors of the conflict. The history factor is lack of understanding of the two martial groupsâ members to their martial groupâs spirit. This is due to the lack of guidance from the elders of the two traditional martial arts groups in guiding the members. While the economic, social, and political factor includes: economic gap between the two institutions. The SH Terate seems to have a better economic, social and political status compare to SH Winongo. The peace settlements had been agreed by both martial groups, however, failed to prevent further violent conflict. This is because the settlement did not touch the basic issues of history, economic, social, and political factors.